Polypharmacy in Older Adults Undergoing Major Surgery: Prevalence, Association With Postoperative Cognitive Dysfunction and Potential Associated Anesthetic Agents - Lertkovit, Saranya; Siriussawakul, Arunotai; Suraarunsumrit, Patumporn; Lertpipopmetha, Wanicha; Manomaiwong, Natapong; Wivatdechakul, Wittachi; Srinonprasert, Varalak (Frontiers in Medicine, 2022)
Background: Polypharmacy, which is defined as the use of 5 or more medications, can exert significant adverse impact on older adult patients. The objective of this study was to determine the prevalence of polypharmacy, and to investigate its association with postoperative cognitive dysfunction (POCD) in older adult patients who underwent elective major surgery at Siriraj Hospital – Thailand’s largest national tertiary referral center. Methods: This prospective study included older adult patients aged ≥65 years who were scheduled for elective major surgery during December, 2017 to December, 2019 study period. Patient demographic, sociodemographic, anthropometric, clinical, comorbidity, anesthetic, surgical, and medication data were collected and compared between the polypharmacy and non-polypharmacy groups. Postoperative cognitive dysfunction (POCD) was diagnosed in patients with at least a 2-point decrease in their Montreal Cognitive Assessment score after surgery. Multivariate logistic regression analysis was used to identify independent predictors of POCD. Results: A total of 250 patients (141 males, 109 females) with an average age of 72.88±6.93 years were included. The prevalence of polypharmacy was 74%. Preoperative data showed the polypharmacy group to be more likely to be receiving potentially inappropriate medications, to be scheduled for cardiovascular thoracic surgery, and to have more comorbidities. There was a non-significant trend in the association of polypharmacy and POCD (crude odds ratio (OR): 2.11, 95% confidence interval [CI]: 0.90-4.94; p=0.08). Benzodiazepine, desflurane, or isoflurane administration during surgery were all significantly associated with POCD in univariate analysis. Multivariate analysis revealed intraoperative benzodiazepine (adjusted OR [aOR]: 2.24, 95% CI: 1.10-4.68; p=0.026) and isoflurane (aOR: 2.80, 95% CI: 1.35-5.81; p=0.006) as two independent variables associated with the development of POCD. Desflurane was found to be a protective factor for POCD with a crude OR of 0.17 (95% CI: 0.03-0.74, p=0.019); however, independent association was not found in multivariate analysis. Conclusion: There was a high prevalence of polypharmacy in this study; however, although close (p=0.08), significant association was not found between polypharmacy and POCD. Benzodiazepine and isoflurane were both identified as independent predictors of the development of POCD among older adult patients undergoing elective major surgery, especially among those classified as polypharmacy.